Enhancement of critical current density in CaKFe4As4 single crystals through 3 MeV proton irradiation - Haberkorn, N. (2020)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina; Iowa State University; Estados Unidos